Development information and tools about disaster: Among children at primary school - Kamarudin, Muhamad Amirul Solehin Nor; Chong, Khai Lin (Universiti Utara Malaysia, 2020)
Disaster is an unexpected event and brings a very bad catastrophe. This situation happened suddenly, had negative impact to the disaster victims especially children. Therefore, the purpose of this study to handle this problem is by developing information and tools about disaster risk for school children is the best way to educate them to face disaster strikes when it happens suddenly. By using quantitative research method, the data is collected through questionnaire. The respondent involves 30 respondents of students ‘Sekolah Kebangsaan Felda Bukit Tangga’ and the data is analyzed using SPSS. The data get from questionnaire and result shows 93% student agree that information is good, fun and useful learning material to children, may help parents and teachers in guiding and assisting children to create their awareness on safety about disaster. It is recommended disaster education must be implemented in worldwide curriculum